γ Irradiation of Staphylococcal Enterotoxin B - Read, R. B. (1967)
The inactivation of enterotoxin B by γ irradiation was studied by use of single-and double-gel-diffusion assay techniques. Enterotoxin B (99+% purity) was suspended either in 0.04 m Veronal buffer (pH 7.2) or in milk, dispensed and heat-sealed in borosilicate glass vials, and irradiated essentially at 21 to 26 C with a cobalt-60 source. Parallel titrations of irradiated enterotoxin B in Veronal buffer were made by use of gel-diffusion and cat assay procedures to establish the relative sensitivity of these two assay procedures to irradiated enterotoxin. Results were identical. A dose of 5 Mrad was required to reduce an enterotoxin B concentration of 31 μg/ml in Veronal buffer to less than 0.7 μg/ml. When milk was used as a vehicle, a dose of 20 Mrad was needed to inactivate a 30 μg/ml concentration of enterotoxin B to less than 0.5 μg/ml. With Veronal buffer and milk as vehicles, the D values (dose required to inactivate 90%) for enterotoxin B inactivation were 2.7 and 9.7 Mrad, respectively.